Runoff and Sediment from Row-crop, Row-crop with Grass Strips, Pasture, and Forest Watersheds - Udawatta, Ranjith; Henderson, Gray; Jones, John; Hammer, R. (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2006)
AbstractComparisons of runoff and sediment loss from row-crop with and without riparian buffers, pasture and grass filter strips are limited. Effects of precipitation, landuse and buffer condition on runoff and sediment loss were examined from 1997 to 1999 in eight watersheds with varying proportions of row-crop, pasture, riparian buffers and grass filter strips. Runoff volume and sediment mass from row-crop watersheds were inversely related to the percentage of forest and pasture cover. Forest (n = 2), pasture (n = 3), row-crop (n = 2) and a row-crop watershed with grass filter strips (RC-GFS) had 3‑yr mean runoff of 939, 1,560, 3,434 and 1,175 m3 ha‑1 yr‑1, respectively. Runoff was greater from all landuses in a year when precipitation was 36% above normal (1998). The largest single runoff event from each watershed accounted for 11 to 25% of its total runoff. Forest, pasture, row-crop and RC-GFS watersheds lost 1,017, 1,241, 3,679 and 2,129 kg ha‑1 yr‑1 of sediment, respectively. In 1998, the RC-GFS watershed lost more sediment than row-crop watersheds and had less runoff and sediment loss in years with normal or below normal precipitation. Row-crop watersheds with 55% pasture reduced runoff and sediment loss by 55 and 66%, respectively, compared to row-crop watersheds. During 90% of the runoff events, more soil was lost from row-crop watersheds than pasture or forest watersheds. Results suggest that 3‑4 m grass filter strips, maintenance of 55% or more pasture/CRP land within row-crop watersheds and intact riparian buffers significantly reduce runoff and sediment losses from row-crop watersheds.